Le pouvoir de l’image : le Mois de la Photo à Montréal, 2001 - Bellavance, Guy (CV Photo)

(untitled) (Les Productions Ciel variable, 2002)
This commentary on The Power of the Image, the seventh edition of Mois de la Photo à Montréal, emphasizes the presence this year of three fundamental trends: postcolonialism, deconstruction of the image, and interventions in the public space. Within each of these trends, the author notes the particular interest in certain proposed visions: the Shirin Neshat retrospective, in relation to the postcolonial movement; the projects by Emmanuelle Léonard and Alain Declercq, in relation to interventions in the urban space; and with regard to deconstruction, the video-film installation by Mark Lewis and the photo-video exhibition De quelques rituels masculins.